The effects of maize cobs and supplemental rumen-protected conjugated linoleic acid (CLA) on production efficiency and meat quality characteristics of South African mutton merinos - Rousseau, Francois Jacques (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric) -- University of Stellenbosch, 2006.